Do firms in rural regions lack access to credit? Local variation in small business loans and firm growth. Issue 11 (2nd November 2022) - Kärnä, Anders; Stephan, Andreas
ABSTRACT: We investigate whether bank loans specifically designed to reduce credit constraints for small and medium-sized enterprises (SMEs) have different impacts depending on where the firm is located. Using detailed firm-level data from the state-owned Swedish bank Almi, which specifically lends to credit-constrained SMEs, and coarsened exact matching and difference-in-difference regressions, we study the causal effects of small business loans on firm growth. The results show that receiving a loan has a greater impact on firm growth for those SMEs located in major cities than for firms located in remote rural regions. This result has implications for policies that aim to increase growth in rural regions and suggests that increasing access to credit alone is not sufficient to increase employment growth.